Interaction between two solitons in two-dimensional complex plasma with variable dust charge - Mahdizadeh, N.; Aslaninejad, M. (Вопросы атомной науки и техники, 2009)
We have studied the propagation of the dust acoustic solitary waves in two different directions for a non-magnetized, two dimensional dusty plasma including the variation of dust charges. We extend the reductive perturbation method and obtain two KdV equations for a nonlinear wave in two different directions. We also compare our results with the case of constant dust charge.